Unstable Type III Wrisberg-type Lateral Discoid Meniscus: All-inside Arthroscopic Repair. Issue 3 (April 2021) - Grassi, Alberto; Pizza, Nicola; Macchiarola, Luca; Zaffagnini, Stefano
Background: The Type III Wrisberg-type represents the rarest subtype of discoid meniscus. It exhibits a normal non-discoid "C"-shape with possible posterior horn hypertrophy, but meniscotibial ligaments and capsular restraints are lacking, leading to a clinical scenario of knee pain, popping, and catching due to meniscal hypermobility. Moreover, concomitant tears can be present due to repeated meniscal traumas. Indications: Type III Wrisberg-type lateral discoid meniscus with hypermobility, dislocation, or tear. Technique Description: Through standard arthroscopic portals, the meniscus is reduced in its anatomical position (if displaced). Abnormal mobility and anatomy should be noted. All-inside sutures are used in the posterior horn and body to stabilize the meniscus to the capsule and popliteus tendon. In the case of radial tears, horizontal stitches are used. Results: Patients are expected to return to sport approximately 4 to 5 months after the procedure with relief of pain, popping sensation, and knee locking. Conclusion: Arthroscopic all-inside repair is an effective treatment for unstable and displaced Type III Wrisberg-type lateral discoid meniscus. However, the diagnosis can be challenging, especially without frank meniscal dislocation. Graphical Abstract This is a visual representation of the abstract.